2020
DOI: 10.1002/hed.26386
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of distant metastases in patients with squamous cell carcinoma of head and neck using DWI and DCE‐MRI

Abstract: Background: The primary purpose was to evaluate the prognostic potential of diffusion imaging (DWI) and dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) in predicting distant metastases in squamous cell carcinoma of head and neck (HNSCC) patients. The secondary aim was to examine differences in DWI and DCE-MRI-derived parameters on the basis of human papilloma virus (HPV) status, differentiation grade, and nodal stage of HNSCC. Methods: Fifty-six patients underwent pretreatment DWI and DCE-MRI. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Overall, low risk of bias was selected most often in all assessment categories, except for the reference standard, for which high risk was most prevalent. For the reference standard, the main concern was the use of different HPV determination methods for different patients or the exclusive use of p16 immunohistochemistry for HPV determination [ 20 , 21 , 22 , 23 , 26 , 31 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The main concern for patient selection was the lack of information on consecutive or random patient selection and the exclusion of patients with lower-stage OPSCC [ 20 , 25 , 27 , 35 , 36 , 37 , 38 , 39 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, low risk of bias was selected most often in all assessment categories, except for the reference standard, for which high risk was most prevalent. For the reference standard, the main concern was the use of different HPV determination methods for different patients or the exclusive use of p16 immunohistochemistry for HPV determination [ 20 , 21 , 22 , 23 , 26 , 31 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The main concern for patient selection was the lack of information on consecutive or random patient selection and the exclusion of patients with lower-stage OPSCC [ 20 , 25 , 27 , 35 , 36 , 37 , 38 , 39 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…For the reference standard, the main concern was the use of different HPV determination methods for different patients or the exclusive use of p16 immunohistochemistry for HPV determination [ 20 , 21 , 22 , 23 , 26 , 31 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. The main concern for patient selection was the lack of information on consecutive or random patient selection and the exclusion of patients with lower-stage OPSCC [ 20 , 25 , 27 , 35 , 36 , 37 , 38 , 39 , 45 , 46 , 47 ]. Regarding the index test, the main concern was the lack of pre-specification of thresholds or independent validation [ 21 , 25 , 26 , 27 , 31 , 39 , 40 , 41 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 Dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) is another promising imaging technique that provides quantitative and biologically relevant information related to perfusion characteristics of metastatic lymph nodes in the entire neck region. 13,14 Numerous studies have shown the clinical potential of DCE-MRI derived parameters in predicting and evaluating treatment response to induction chemotherapy 15 and concurrent chemo-radiation therapy [16][17][18][19][20][21][22] in HNSCC. Collectively, these studies have suggested that patients harboring high pretreatment tumor perfusion respond more favorably to therapies and demonstrate improved disease-free and overall survival outcomes.…”
Section: Introductionmentioning
confidence: 99%